Perioperative neurocognitive disorder in colorectal cancer surgery: a systematic review of incidence, mechanisms, and interventions - Huang, Xiujin; Quan, Zongjie; Zhan, Chenyang; Sandeep, Bhushan; Bu, Jun (Frontiers in Surgery, 2025)
BackgroundPerioperative neurocognitive disorder (PND) represents a significant impediment to postoperative recovery in patients undergoing colorectal cancer surgery, particularly among the elderly. This systematic review synthesizes contemporary evidence on PND incidence, risk stratification, and prophylactic strategies.MethodsAdhering to PRISMA guidelines, 343 records were identified from PubMed, Embase, and Web of Science. Bibliometric profiling delineated influential journals, institutions, and seminal references. Following deduplication and screening, 11 randomized controlled trials (RCTs) met inclusion criteria for systematic analysis.ResultsBibliometric analysis revealed Journal of Geriatric Oncology (impact factor 2.7) and Amphia Hospital (Netherlands) as top contributors. PND incidence ranged from 3.4% to 56% across studies. Key risk factors included advanced age (mean 63–76 years), ASA status II–III, and open surgery. Prophylactic interventions reduced PND: melatonin decreased POD by 20%; dexmedetomidine reduced PND by 10.8%–25%. Fast-track surgery lowered POD by 9.5%. Mechanistically, effective strategies attenuated neuroinflammation (IL-6/TNF-α reduction) and optimized analgesia.ConclusionsMultimodal interventions—especially dexmedetomidine-enhanced analgesia and fast-track protocols—consistently mitigate PND. Standardization of PND assessment tools and diversification of study populations are urgently needed.